Pengembangan Aplikasi Simulasi Perdagangan Saham dengan Sector Rotation dan Linear Programming - Tomy G. Soemapradja; Jerry Marcellinus Logahan; Hengky Ongowarsito (Binus Business Review, 2014)
In strategic development a university will shift from teaching university to research university. It is because academic outcomes will be more useful if they can be commercialized by industries, which help improve the ranking of a university. The development of capital market and management measures of Indonesia Stock Exchange during the last 8 years aiming at academicians in order to identify and be interested in investing in the stock market needs to be observed. That is by providing a simulation so that more students can improve the competition at their graduation. The involvement of industry selection strategy and portfolio management will be required so that the expertise and ability to manage investments in the capital market can be better. So, it necessarily requires a development of simulation application of stock trading with business rotation and linear programming.